Pengaruh Promosi dan Kesadaran Merek sebagai Variabel Mediasi terhadap Keputusan Pembelian Produk Wafer Tango di Wilayah Surabaya - Aidhaningtyas, Fera Tri; Purwanto, Sugeng (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of promotion and brand awareness on purchasing decisions and to examine the role of brand awareness as a mediating variable between promotion and purchasing decisions on Wafer Tango in Surabaya region. The population in this study were all people who had bought and consumed Wafer Tango in Surabaya, the sampling technique used was non-probability sampling, so that the results obtained were 104 respondents. The measurement scale used in this studi is the Likert Scale. The data collection method used is by distributing questionnaires containing questions to respondents througt the Google Form. The data analysis technique is Partial Least Square (PLS) with validity test, reliability test, and hypothesis testing. The results of this tsudy that the promotion variable has a positive effect on brand awareness and also the purchasing decision. Furthermore, the brand awareness variable has a positive effect on purchasing decisions. As well as brand awareness variables can be used as mediating variables between promotion variables and purchasing decisions variables. Keywords : Brand Awareness; Promotion; Purchasing Decision.